Structural Health and the Politics of African American Masculinity - Jonathan M. Metzl MD, PhD (American Journal of Men's Health, 2013)
This commentary describes ways in which notions of African American men’s “health” attained by individual choice—embedded in the notion that African American men should visit doctors or engage in fewer risky behaviors—are at times in tension with larger cultural, economic, and political notions of “health.” It argues that efforts to improve the health of Black men must take structural factors into account, and failure to do so circumvents even well-intentioned efforts to improve health outcomes. Using historical examples, the article shows how attempts to identify and intervene into what are now called social determinants of health are strengthened by addressing on-the-ground diagnostic disparities and also the structural violence and racism embedded within definitions of illness and health. And, that, as such, we need to monitor structural barriers to health that exist in institutions ostensibly set up to incarcerate or contain Black men and in institutions ostensibly set up to help them.